Literasi Pajak dan Keuangan: Optimalisasi Peningkatan Kompetensi UMKM di Jayapura - Meinarni Asnawi; Ulfah Rizky Muslimin (UNIVERSITAS CENDERAWASIH, 2022)
This community service aims to provide knowledge about digitalization in the field of taxation and business for UMKM in Jayapura. The change in the business world towards the era of information technology is a progress that has been going on for approximately 10 years. The Covid-19 pandemic has made business activities change so fast and allowed all lines of business to develop, including UMKM sector. Introducing digitalization and taxes is important for UMKM to prepare themselves to develop their business potential. The process of financial recording and reporting, digital business design and the benefits of being a taxpayer are the main materials provided for UMKM. Public services are focused on three materials, namely tax digitalization literacy, financial digitalization literacy, and business digitalization. Tax literacy introduces UMKM to the benefits of taxes and the procedures also methods of becoming a taxpayer. Business literacy focuses on the introduction of information technology-based financial records and business digitalization. The participants of this service are UMKM in Jayapura City and Accounting students who are doing KKN and become UMKM companions. The teaching method is carried out online with 48 participants then the mentoring process is carried out by KKN students to ensure that the material presented can be applied in the efforts of UMKM members. Through learning methods that are delivered directly to experts in their fields and followed by a mentoring process, knowledge transfer occurs and UMKM can develop their businesses.